A method for depolymerizing lignin, depolymerization product and application thereof
By using a bifunctional solvent to perform depolymerization reaction with lignin, the problem of low reaction activity of industrial lignin is solved, and efficient lignin depolymerization is achieved. The obtained oligomer is used to prepare polyurethane materials with excellent performance, which improves the replacement amount of petroleum-based polyether and the biodegradability of the material.
Patent Information
- Application Number
- CN202310434877.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-21
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2043-04-21
AI Technical Summary
In the prior art, the composition of industrial lignin is complex and has low reactivity, resulting in low reactivity of lignin and isocyanate, and it is impossible to form a polyurethane material with excellent performance and uniform performance.
The depolymerization reaction is carried out by mixing a bifunctional solvent with lignin, and the oligomer with an appropriate molecular weight distribution is obtained through filtration, water precipitation, centrifugal separation, and drying under reduced pressure.
The high molecular weight industrial lignin is depolymerized into low molecular weight lignin oligomers under mild conditions, which improves the performance of polyurethane materials and the replacement amount of petroleum-based polyethers, and reduces raw material costs and environmental pollution.
Smart Images

Figure BDA0004191696060000101 
Figure BDA0004191696060000111 
Figure BDA0004191696060000112
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of green utilization of agricultural and forestry waste resources, and in particular to a lignin depolymerization method, a depolymerization product and an application thereof. Background Art
[0002] As a major agricultural country, my country has abundant lignin resources. However, according to statistics, only about 2-5% of lignin is used to produce fine chemical products such as additives, adsorbents and surfactants and modified polymer materials each year. Most lignin is burned as low-quality fuel or discarded as waste, which not only has low economic benefits, but also causes environmental pollution problems. The lignin-based polyurethane materials produced from lignin not only have the general characteristics of petroleum-based polyurethane materials, but also have special properties such as degradability, radiation protection, and antibacterial properties. In particular, due to the richness and renewable characteristics of lignin raw materials, it has become an ideal substitute for petroleum-based polyurethane materials, and has strong market competitiveness and future application and promotion prospects. Therefore, the development of lignin-based degradable polyurethane materials can greatly reduce the consumption of petroleum resources, achieve significant carbon emission reduction, and reduce the low resource utilization efficiency and environmental pollution problems caused by the treatment of waste polyurethane materials.
[0003] Although lignin has significant advantages in preparing polyurethane materials, the current use of industrial lignin raw materials has the following problems: the composition of industrial lignin is complex, the molecular weight of lignin is high, the dispersion is high, the hydroxyl content of lignin raw materials is low (generally 30-40 mgKOH / g), the reaction activity is low, and the dispersion is uneven. This leads to low activity of lignin in the reaction with isocyanate, and the cross-linking characteristics of the system are uneven, and it is impossible to form a polyurethane material with excellent performance and uniformity. The core problem is how to depolymerize industrial lignin into oligomers with a suitable molecular weight distribution. Through the study of the controllable depolymerization law of industrial lignin, it is hoped that depolymerized lignin raw materials with molecular weight and distribution that meet the requirements of use can be obtained; at the same time, hydroxyl groups are released during the depolymerization process, and the methoxy groups on the benzene ring are converted into phenolic hydroxyl groups through the application of functional catalysts, thereby increasing the number of active functional groups and improving the distribution uniformity. Therefore, how to obtain an efficient method for depolymerization of lignin has become one of the scientific supports and prerequisites for its efficient and large-scale utilization.
[0004] From the perspective of cost, efficiency and technical reliability, the new method of lignin degradation shows that the thermochemical conversion method has greater potential for industrial application. According to different treatment processes, the thermochemical method is divided into high-temperature pyrolysis, hydrogenolysis, gasification, solvent thermal, oxidation and combustion. Among them, the products of high-temperature pyrolysis and catalytic depolymerization are mainly liquid phenol monomer products. High-temperature pyrolysis usually does not use a catalyst. In the presence of air at high temperature, biomass is converted into gas, pyrolysis oil and coke. Factors affecting the distribution and composition of lignin pyrolysis products include heating rate, pyrolysis temperature, reaction time, reaction pressure and raw material characteristics. According to the different heating rates in the reaction, pyrolysis liquefaction can be divided into slow pyrolysis, medium-speed pyrolysis and fast pyrolysis. The slow pyrolysis product is mainly coke; the yields of gas, liquid and solid products of medium-speed pyrolysis are basically equal; the yield of liquid products of fast pyrolysis at 500-600°C is 80%. The obtained gas, liquid and coke can all be used as fuel. As early as the 1980s, the University of Waterloo in Canada developed a pressurized fluidized bed pyrolysis process and used fluidized bed rapid pyrolysis technology to study wood biomass. The Renewable Energy Laboratory in the United States developed the latest ablative vortex reactor, and James Diebold and others studied the vortex reactor pyrolysis technology. Many domestic scientific research institutions are studying new technologies for high-temperature pyrolysis and liquefaction of biomass.
[0005] Catalytic depolymerization method: The catalytic depolymerization of lignin refers to a chemical reaction process at medium and low temperatures, under pressure, and with the participation of a catalyst. Biomass macromolecules are broken into small molecules under the action of a catalyst. These small molecules are unstable and easily repolymerized to form new components with larger molecular weights. Therefore, the liquefied product is a multi-component mixture. The composition and properties of the liquefied product are regulated by changing reaction conditions such as solvent, liquefaction temperature, pressure, and catalyst, in order to obtain liquefied products with different uses. Compared with rapid pyrolysis, the catalytic depolymerization method has the characteristics of mild reaction conditions, relatively simple process technology, low energy consumption in the reaction process, and basically no gas products. However, the product is still a mixture of multiple components, and the direct extraction of key components is still not the first choice because it requires a complex separation process.
[0006] The following key issues need to be addressed in the current research field:
[0007] 1. At present, the degradation products are a mixture of various phenol monomers, which are difficult to separate and have low efficiency in practical application. It is necessary to develop efficient separation technology to obtain single-component raw materials, which can then be used in subsequent fine synthesis processes or to develop new technologies for the use of mixtures. Monophenol products are not suitable for use as raw materials for bio-based polyurethanes. 2. The process conditions of most degradation methods are strict, and the temperature and pressure are relatively high, such as thermal cracking, hydrothermal and catalytic depolymerization methods. 3. The solid catalyst used can efficiently degrade lignin, but the complex catalyst preparation process, catalyst reuse and recycling problems will bring practical difficulties to subsequent industrial amplification applications. 4. Although the process for preparing lignin polyols by direct liquefaction of industrial lignin is mature, the viscosity of the liquefied product is too large and it is difficult to use it directly. Although the viscosity can be reduced by increasing the liquid-to-solid ratio (10:1 or higher), the lignin content in the resulting polyol product is too low, making it a conceptual product.
[0008] Therefore, how to provide a method for depolymerizing lignin and application of its depolymerization products is a technical problem that needs to be solved urgently by those skilled in the art. Summary of the invention
[0009] The purpose of the present invention is to provide a method for depolymerizing lignin, a depolymerization product and an application thereof in view of the deficiencies in the prior art, so as to solve the technical problems existing in the prior art such as complex lignin composition and low reaction activity.
[0010] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0011] The present invention provides a method for depolymerizing lignin, comprising the following steps:
[0012] 1) mixing the bifunctional solvent and lignin and performing a depolymerization reaction to obtain a depolymerization product;
[0013] 2) The depolymerized product is filtered, precipitated with water, centrifuged, and dried under reduced pressure to obtain a depolymerized lignin product;
[0014] The bifunctional solvent is a substance containing characteristic functional groups of guaiacyl, p-hydroxyphenyl or syringyl monomers constituting lignin.
[0015] Preferably, the mass ratio of the bifunctional solvent to lignin is 1.5 to 5:1;
[0016] The lignin is industrial lignin, which includes one or more of sulfonate lignin, alkali lignin, enzymolysis lignin and organic solvent lignin.
[0017] Preferably, the bifunctional solvent is obtained by mixing compound A and compound B in a mass ratio of 8 to 12:1;
[0018] The compound A comprises one or more of phenolic resin oligomers, phenol formaldehyde oligomers, phenol furfural resin oligomers, phenol sugar resin oligomers, o-cresol and o-cresol glycidyl ether;
[0019] The compound B comprises thioglycolic acid and / or tyrosine.
[0020] Preferably, the molecular weights of the phenolic resin oligomer, phenol formaldehyde resin oligomer, phenol furfural resin oligomer and phenol sugar resin oligomer are independently ≤300.
[0021] Preferably, the temperature of the depolymerization reaction is 40 to 120° C., and the time of the depolymerization reaction is 2 to 8 hours.
[0022] Preferably, the reduced pressure drying is carried out at 70 to 90° C. and -0.8 to 0.5 MPa for 2 to 4 hours.
[0023] Preferably, the molecular weight of the lignin is 10,000 to 200,000, and the dispersion degree is 2.0 to 5.0.
[0024] The present invention also provides a depolymerized lignin product obtained by the lignin depolymerization method. The molecular weight of the depolymerized lignin product is 400-1200, and the molecular weight distribution is 1.2-2.0.
[0025] Preferably, the hydroxyl value of the depolymerized lignin product is 400-700 mgKOH / g.
[0026] The invention also provides an application of a depolymerized lignin product in preparing a polyurethane material.
[0027] Beneficial effects of the present invention:
[0028] 1. Design and synthesis of depolymerization aids with dual functions of catalytic depolymerization and dissolution, which can depolymerize industrial lignin raw materials with high molecular weight (10,000 to 100,000) and high dispersion (2.0-5.0) into lignin oligomers with low molecular weight (400-1000) and narrow distribution (1.2-1.5) under mild conditions, which can effectively meet the requirements for the preparation of lignin-based polyurethane. The main methods for preparing polyurethane with lignin at present are direct addition of raw materials, addition after liquefaction, or addition after modification.
[0029] 2. The method achieves the goal of obtaining lignin oligomer products with adjustable molecular weight and distribution by controlling the parameters of the depolymerization process. The products of the current mainstream degradation technology are all phenol monomers, and the depolymerization conditions are relatively strict. Their commonality is that a mixed system of solvent and catalyst is used for degradation. Compared with the technical method of the present invention, the solvent and catalyst need to be recycled using different process methods respectively, and the complexity of the process is higher than that of the method of the present invention.
[0030] 3. The substitution amount of lignin for petroleum-based polyether in the preparation of polyurethane is significantly increased. The low molecular weight (400-1200) depolymerized lignin product obtained by the method of the present invention can still obtain high-quality polyurethane materials at a higher substitution amount of petroleum-based polyether (60-85%) (refer to the data in the subsequent invention examples). The appropriate substitution amount of directly adding lignin raw materials is only 25-30%; the maximum substitution amount of modified lignin is about 50%.
[0031] 4. A degradable polyurethane material with excellent comprehensive properties and low cost was obtained. The hard polyurethane raw material was prepared using depolymerized lignin products with suitable molecular weight and distribution. When the replacement amount of petroleum polyether was 60-85%, the mechanical properties of the obtained polyurethane material were improved by 100-200% compared with similar petroleum-based products. The material has obvious biodegradability, with a degradation rate of up to 75.6%, and the raw material cost was reduced by more than 30%. DETAILED DESCRIPTION
[0032] The present invention provides a method for depolymerizing lignin, comprising the following steps:
[0033] 1) mixing the bifunctional solvent and lignin and performing a depolymerization reaction to obtain a depolymerization product;
[0034] 2) The depolymerized product is filtered, precipitated with water, centrifuged, and dried under reduced pressure to obtain a depolymerized lignin product;
[0035] The bifunctional solvent is a substance containing characteristic functional groups of guaiacyl, p-hydroxyphenyl or syringyl monomers constituting lignin.
[0036] In the present invention, the mass ratio of the bifunctional solvent to lignin is 1.5 to 5:1, preferably 2 to 4:1, and more preferably 3:1;
[0037] The lignin is industrial lignin, which includes one or more of sulfonate lignin, alkali lignin, enzymolysis lignin and organic solvent lignin.
[0038] In the present invention, the particle size of the lignin is 40 to 80 meshes, preferably 45 to 75 meshes, and more preferably 50 to 60 meshes.
[0039] In the present invention, the bifunctional solvent is obtained by mixing compound A and compound B in a mass ratio of 8 to 12:1, preferably 9 to 11:1. More preferably, it is 10:1;
[0040] The compound A comprises one or more of phenolic resin oligomers, phenol formaldehyde oligomers, phenol furfural resin oligomers, phenol sugar resin oligomers, o-cresol and o-cresol glycidyl ether;
[0041] The compound B comprises thioglycolic acid and / or tyrosine.
[0042] In the present invention, the molecular weights of the phenolic resin oligomer, phenol formaldehyde resin oligomer, phenol furfural resin oligomer and phenol sugar resin oligomer are independently ≤300, preferably ≤250, and more preferably ≤200.
[0043] In the present invention, the temperature of the depolymerization reaction is 40 to 120° C., preferably 50 to 110° C., more preferably 60 to 100° C., and the time of the depolymerization reaction is 2 to 8 hours, preferably 3 to 7 hours, more preferably 4 to 6 hours.
[0044] In the present invention, the time for adding water for precipitation is 3 to 5 hours, preferably 3.5 to 4.5 hours, and more preferably 4 hours.
[0045] In the present invention, the reduced pressure drying is carried out at 70 to 90°C and -0.8 to 0.5 MPa for 2 to 4 hours. The temperature of the reduced pressure drying is preferably 75 to 85°C, and more preferably 80°C; the pressure of the reduced pressure drying is preferably -0.5 to 0.4 MPa, and more preferably -0.4 to 0.3 MPa; the time of the reduced pressure drying is preferably 2.5 to 3.5 hours, and more preferably 3 hours.
[0046] In the present invention, the molecular weight of the lignin is 10,000 to 200,000, preferably 50,000 to 150,000, more preferably 80,000 to 130,000, and the dispersion degree is 2.0 to 5.0, preferably 2.5 to 4.5, more preferably 2.7 to 4.3.
[0047] The present invention also provides a depolymerized lignin product obtained by the lignin depolymerization method, wherein the depolymerized lignin product has a molecular weight of 400 to 1200, preferably 500 to 900, more preferably 600 to 800, and a molecular weight distribution of 1.2 to 2.0, preferably 1.3 to 1.6, more preferably 1.4.
[0048] In the present invention, the hydroxyl value of the depolymerized lignin product is 400 to 700 mgKOH / g, preferably 450 to 550 mgKOH / g, and more preferably 470 to 530 mgKOH / g.
[0049] The present invention also provides an application of a depolymerized lignin product in the preparation of a polyurethane material, comprising the following components in parts by mass: X parts of a polyether polyol 303100, X parts of a depolymerized lignin product, 0.6 to 3.5 parts of silicone oil L-580, 1.2 to 4.3 parts of deionized water, and 0.7 to 1.8 parts of a catalyst T-12, wherein the isocyanate index is 0.8 to 1.2.
[0050] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0051] Example 1
[0052] Add 200.0g of 45 mesh alkali lignin (molecular weight 12,000, molecular weight distribution 5.0), 300.0g of a mixture of phenolic resin oligomer (molecular weight 124) and thioglycolic acid in a mass ratio of 10:1 into the reactor, react at 50℃ for 5h, cool down and filter out the undissolved raw materials after the reaction is completed; add 200mL of water to the remaining mixture to precipitate the dissolved depolymerized lignin, let it stand for 3.5 hours, then centrifuge to separate the precipitate, and then dry it under reduced pressure at 85℃ and -0.8MPa for 3 hours to obtain a depolymerized lignin product, the measured mass is 170.8g; the remaining solvent and water mixture is distilled under reduced pressure to separate the water, and the recovered solvent is obtained for repeated use. The average molecular weight of the obtained lignin depolymerization product is 600, the molecular weight distribution is 1.36, the hydroxyl value is 564.0mg KOH / g, and the depolymerization product yield is 85.4%.
[0053] Example 2
[0054] Add 200.0g of 55 mesh alkali lignin (molecular weight 32,000, molecular weight distribution 5.0), 700.0g of a mixture of phenol furfural resin oligomer (molecular weight 213) and tyrosine in a mass ratio of 8:1 into the reactor, react at 70℃ for 3h, cool down and filter out the undissolved raw materials after the reaction; add 240mL of water to the remaining solvent to precipitate the dissolved depolymerized lignin, let it stand for 5 hours, then centrifuge to separate the precipitate, and then pressurize and dry at 90℃ and 0.5MPa for 2 hours to obtain the depolymerized lignin product, the measured mass is 185.4g; the remaining solvent and water mixture is distilled under reduced pressure to separate the water, and the recovered solvent is obtained for repeated use. The average molecular weight of the obtained lignin depolymerization product is 420, the molecular weight distribution is 1.54, the hydroxyl value is 620.6mg KOH / g, and the depolymerization product yield is 92.7%.
[0055] Example 3
[0056] Add 200.0g of 80-mesh organic solvent lignin (molecular weight 120,000, molecular weight distribution 3.9) and 750.0g of a mixture of o-cresol and thioglycolic acid in a mass ratio of 12:1 to the reactor, react at 90°C for 8h, cool down and filter out the undissolved raw materials after the reaction is completed; add 300mL of water to the remaining solvent to precipitate the dissolved depolymerized lignin, let it stand for 4 hours, then centrifuge to separate the precipitate, and then dry it under reduced pressure at 80°C and -0.7MPa for 3 hours to obtain a depolymerized lignin product, the mass after measurement is 175.2g; the remaining solvent and water mixture is distilled under reduced pressure to separate the water therein, and the recovered solvent is obtained for repeated use. The average molecular weight of the obtained lignin depolymerization product is 1080, the molecular weight distribution is 1.72, the hydroxyl value is 478.0mg KOH / g, and the depolymerization product yield is 87.6%.
[0057] Example 4
[0058] Add 200.0g of 65-mesh alkali lignin (molecular weight 32,000, molecular weight distribution 5.0), 700.0g of a mixture of phenol furfural resin oligomer (molecular weight 213) and tyrosine in a mass ratio of 11:1 to the reactor, react at 70°C for 3h, cool down and filter out the undissolved raw materials after the reaction is completed; add 280ml of deionized water to the remaining solvent to precipitate the dissolved depolymerized lignin, let it stand for 3 hours, then centrifuge to separate the precipitate, and then dry it under reduced pressure at 85°C and -0.8MPa for 2 hours to obtain a depolymerized lignin product, the mass after measurement is 185.2g; the remaining solvent and water mixture is distilled under reduced pressure to separate the water therein, and the recovered solvent is obtained for repeated use. The average molecular weight of the obtained lignin depolymerization product is 562, the molecular weight distribution is 1.52, the hydroxyl value is 587.5mg KOH / g, and the yield of the depolymerization product is 92.6%.
[0059] Example 5
[0060] Add 200.0g of 75-mesh organic solvent lignin (molecular weight 120,000, molecular weight distribution 3.9) and 600.0g of a mixture of o-cresol and tyrosine in a mass ratio of 9:1 into the reactor, react at 120℃ for 3h, cool down and filter out the undissolved raw materials after the reaction is completed; add 250ml of deionized water to the remaining solvent to precipitate the depolymerized lignin dissolved therein, let it stand for 4.5 hours, then centrifuge to separate the precipitate, and then dry it under reduced pressure at 85℃ and -0.7MPa for 4 hours to obtain the depolymerized lignin product, the measured mass is 191.1g; the remaining solvent and water mixture is distilled under reduced pressure to separate the water therein, and the recovered solvent is obtained for repeated use. The average molecular weight of the obtained lignin depolymerization product is 1200, the molecular weight distribution is 1.64, the hydroxyl value is 421.0mg KOH / g, and the depolymerization product yield is 95.6%.
[0061] Example 6
[0062] Add 200.0g of 70-mesh enzymatic lignin (molecular weight 95,000, molecular weight distribution 4.2) and 500.0g of a mixture of o-cresol glycidyl ether and tyrosine in a mass ratio of 10:1 into the reactor, react at 100℃ for 5h, cool down and filter out the undissolved raw materials after the reaction is completed; add 220mL of deionized water to the remaining solvent to precipitate the dissolved depolymerized lignin, let it stand for 3 hours, then centrifuge to separate the precipitate, and then pressurize and dry at 70℃ and 0.4MPa for 3 hours to obtain the depolymerized lignin product, the measured mass is 181.6g; the remaining solvent and water mixture is distilled under reduced pressure to separate the water, and the recovered solvent is obtained for repeated use. The average molecular weight Mn of the obtained lignin depolymerization product is 1105, the molecular weight distribution is 1.43, the hydroxyl value is 447.4mg KOH / g, and the yield of the depolymerization product is 90.8%.
[0063] Example 7
[0064] Add 200.0g of 60-mesh alkali lignin (molecular weight 32,000, molecular weight distribution 5.0), 500.0g of a mixture of phenol sugar resin oligomer (molecular weight 253) and thioglycolic acid in a mass ratio of 11:1 into the reactor, react at 80°C for 6h, cool down and filter out the undissolved raw materials after the reaction is completed; add 160mL of deionized water to the remaining solvent to precipitate the dissolved depolymerized lignin, let it stand for 5 hours, then centrifuge to separate the precipitate, and then dry it under reduced pressure at 75°C and -0.6MPa for 2 hours to obtain a depolymerized lignin product, the measured mass of which is 176.4g; the remaining solvent and water mixture is subjected to reduced pressure distillation to separate the water therein, and the recovered solvent is obtained for repeated use. The average molecular weight of the obtained lignin depolymerization product is 866, the molecular weight distribution is 1.27, the hydroxyl value is 538.2mg KOH / g, and the yield of the depolymerization product is 88.2%.
[0065] Example 8
[0066] Add 200.0g of 40-mesh sulfonate lignin (molecular weight 120,000, molecular weight distribution 3.9) and 400.0g of a mixture of o-cresol glycerol ether and thioglycolic acid in a mass ratio of 11:1 into the reactor, react at 80°C for 7h, cool down and filter out the undissolved raw materials after the reaction is completed; add 120ml of deionized water to the remaining solvent to precipitate the dissolved depolymerized lignin, let it stand for 5 hours, then centrifuge to separate the precipitate, and then dry it under reduced pressure at 85°C and -0.8MPa for 3 hours to obtain a depolymerized lignin product, the measured mass of which is 182.8g; the remaining solvent and water mixture is subjected to reduced pressure distillation to separate the water therein, and the recovered solvent is obtained for repeated use. The average molecular weight of the obtained lignin depolymerization product is 724, the molecular weight distribution is 1.23, the hydroxyl value is 567.8mg KOH / g, and the yield of the depolymerization product is 91.4%.
[0067] The following Examples 9 to 16 are specific implementation processes for preparing polyurethane materials using the depolymerization products of Examples 1 to 8 and the performance data of the obtained materials. The performance of the degradable polyurethane material prepared from the depolymerization product is tested using the test method specified in the industry standard; the degradation rate of the material is measured using the outdoor soil burial natural degradation method; the thermal decomposition temperature of the material is measured using the thermogravimetric analysis method; and the microstructure of the material is analyzed using the SEM analysis method. The specific analysis method and process are described below.
[0068] 1) Compression strength test
[0069] The compressive strength of polyurethane foam was tested according to the standard of "GB / T8813-2008". A 50mm×50mm×50mm sample was prepared and tested using a MWD-J150 universal testing machine. The compression deformation of the sample was 10% and the compression rate was 5mm·min -1 , take five polyurethane foams prepared under the same conditions and take their average value of the compression strength.
[0070] 2) Thermal conductivity test
[0071] The thermal conductivity of flame retardant polyurethane foam was tested according to the standard of "GB / T10294-2008". The polyurethane foam was cut into 50mm×50mm×5mm samples to be tested. The samples were placed at room temperature for 12 hours and tested using a DZDR-S thermal conductivity meter. The test power was 0.17W and the test time was 160s. Five polyurethane foams prepared under the same conditions were taken, and the thermal conductivity was taken as the average of the five times.
[0072] 3) Thermal stability analysis (TG)
[0073] The thermal stability of polyurethane foam was tested using a STA6000 thermogravimetric analyzer (TG). The thermal degradation rate of polyurethane foam at different temperatures was analyzed. N2 was used as the purge gas and protective gas. The N2 flow rate was 20 mL / min. The temperature range was 50-800 °C, and the heating rate was 10 °C min. -1 .
[0074] 4) Surface morphology (SEM) analysis
[0075] The surface morphology of the foam sample was analyzed by scanning electron microscopy. The polyurethane foam was made into a 50mm×5mm×5mm sample, and the brittle fractured sample was glued to the test bench. The test bench and the sample cross section were then sprayed with gold to increase conductivity and observe the microstructure of the polyurethane foam surface.
[0076] 5) Limiting oxygen index (LOI) determination
[0077] According to the method described in the "GB / T2406.2-2009" standard, the limiting oxygen index (LOI) of the flame retardant polyurethane foam was measured using an M606B oxygen index meter. The polyurethane foam was made into a 120mm×6.5mm×3.0mm sample to be tested, and three polyurethane foams prepared under the same conditions were taken, and the test results were averaged.
[0078] 6) Apparent density test
[0079] The apparent density of flame retardant polyurethane foam was tested according to the standard of "GB / T6343-2009". A 50mm×50mm×50mm sample was prepared and the mass of the sample was weighed. Five polyurethane foams prepared under the same conditions were taken and the average value of the test results was taken.
[0080] 7) The degradation rate of the polyurethane material was determined as follows.
[0081] The experimentally determined process and process formula for synthesizing polyurethane materials from depolymerized lignin products are as follows:
[0082] The polyurethane foam was prepared by a one-step all-water foaming method. The specific foaming steps were as follows: polyether polyol 303, depolymerized lignin, dibutyltin dilaurate, deionized water and silicone oil L580 were added to a 500 mL plastic cup and stirred at 1000 r / min for 2 h. -1 ) Stir for 12 to 15 seconds, calculate the amount of isocyanate added by the isocyanate index, pour into a plastic cup and continue stirring (1000 r / min -1 ) for 15 to 30 seconds. After stirring, the mixture is poured into a foaming mold and freely foamed at room temperature 25°C. After aging for 24 hours, lignin-based polyurethane foam is prepared.
[0083] The formula design for preparing lignin-based polyurethane foam is shown in Table 1 below.
[0084] Table 1 Process formula for preparing lignin-based polyurethane foam
[0085] Components Dosage (portion) Polyether polyol 303 100-X Depolymerization of lignin products X Silicone oil L-580 0.6~3.5 Deionized water 1.2~4.3 Catalyst T-12 0.7~1.8 Isocyanate Index 0.8~1.2
[0086] The raw material ratios of Examples 9 to 16 are shown in Table 2 below:
[0087] Table 2 Polyurethane materials prepared from depolymerized lignin products with different molecular weights and distributions
[0088]
[0089]
[0090] Examples 9 to 16 respectively use the depolymerized lignin products obtained in Examples 1 to 8 as raw materials, and prepare polyurethane foams according to the auxiliary agent formula in Table 1, wherein the replacement amount of the depolymerized lignin product is 50%. The properties of the prepared lignin polyurethanes are listed in Table 3. Table 3 also shows the properties of the polyurethane materials obtained in the comparative example - no lignin addition, modified lignin, and lignin raw materials at a replacement amount of 50%.
[0091] Table 3 Molecular weight of depolymerized lignin raw materials and properties of polyurethane materials prepared therefrom
[0092]
[0093] Table 4 shows that the depolymerized lignin product with a molecular weight of 562 prepared in Example 4 is used as a raw material. Compared with Example 12, by changing the substitution amount of petroleum-based polyether polyol while keeping the amount of other raw materials unchanged, polyurethane foam materials with different petroleum-based polyether substitution amounts are prepared, and the influence of the substitution amount of petroleum-based polyether on the comprehensive performance of the prepared polyurethane material is obtained.
[0094] Table 4 Effect of the substitution amount X of petroleum-based polyether polyol on the comprehensive properties of the prepared polyurethane
[0095]
[0096] As can be seen from the above embodiments, the present invention provides a method for depolymerizing lignin, its products and applications. It can be seen from the experimental data that by designing and synthesizing a depolymerization aid with dual functions of catalytic depolymerization and dissolution, it is achieved that under mild conditions, industrial lignin raw materials with high molecular weight (10,000 to 100,000) and high dispersity (2.0-5.0) are efficiently depolymerized into lignin oligomers with low molecular weight (400-1200) and narrow distribution (1.2-2.0), and the yield of the depolymerization product is as high as 95.6%. By changing the parameters of the depolymerization process, lignin oligomer products with adjustable molecular weight and distribution can be obtained. The lignin oligomer product can be directly used to prepare polyurethane materials, and a degradable polyurethane material with excellent comprehensive properties and low cost can still be prepared at a higher petroleum-based polyether substitution amount (60-85%). The mechanical properties of the obtained polyurethane material are improved by 100-200% compared with similar petroleum-based products, the material has excellent biodegradability, the degradation rate can reach 75.6%, and the raw material cost can be reduced by more than 30%.
[0097] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for depolymerizing lignin, characterized in that: The following steps are involved: 1) mixing the bifunctional solvent and lignin and performing a depolymerization reaction to obtain a depolymerization product; 2) The depolymerized product is filtered, precipitated with water, centrifuged, and dried under reduced pressure to obtain a depolymerized lignin product; The bifunctional solvent is a substance containing characteristic functional groups of guaiacyl, p-hydroxyphenyl or syringyl monomers constituting lignin; The bifunctional solvent is obtained by mixing compound A and compound B in a mass ratio of 8 to 12:1; The compound A comprises one or more of phenolic resin oligomers, phenol formaldehyde oligomers, phenol furfural resin oligomers, phenol sugar resin oligomers, o-cresol and o-cresol glycidyl ether; The compound B comprises thioglycolic acid and / or tyrosine; The mass ratio of the bifunctional solvent to lignin is 1.5-5:
1.
2. The method for depolymerizing lignin according to claim 1, characterized in that The lignin is industrial lignin, which includes one or more of sulfonate lignin, alkali lignin, enzymolysis lignin and organic solvent lignin.
3. The method for depolymerizing lignin according to claim 1 or 2, characterized in that: The molecular weights of the phenolic resin oligomer, phenol formaldehyde oligomer, phenol furfural oligomer and phenol sugar resin oligomer are independently ≤300.
4. The method for depolymerizing lignin according to claim 2, characterized in that: The temperature of the depolymerization reaction is 40 to 120° C., and the time of the depolymerization reaction is 2 to 8 hours.
5. The method for depolymerizing lignin according to claim 1, 2 or 4, characterized in that: The reduced pressure drying is carried out at 70 to 90° C. and -0.8 to 0.5 MPa for 2 to 4 hours.
6. The method according to claim 5, characterized in that The molecular weight of the lignin is 10,000 to 200,000, and the dispersion degree is 2.0 to 5.
0.
7. The depolymerized lignin product obtained by the method for depolymerizing lignin according to any one of claims 1 to 6, characterized in that: The molecular weight of the depolymerized lignin product is 400-1200, and the molecular weight distribution is 1.2-2.
0.
8. The depolymerized lignin product according to claim 7, characterized in that The hydroxyl value of the depolymerized lignin product is 400-700 mgKOH / g.
9. Use of the depolymerized lignin product according to claim 7 or 8 in the preparation of polyurethane materials.
Citation Information
Patent Citations
Methods for controlling depolymerization of polymer compositions
CA2835695A1
Methods for lignin depolymerization using thiols
US20200048292A1